French Public Supports NATO Enlargement, But Many Are Uninformed about the Issues. - United States Information Agency. Office of Research and Media Reaction.; White, B. Susan. (Tufts University. Tisch Library., 2019)
KEY FINDINGS: The French public tends to support NATO's admission of Poland, Hungary and the Czech Republic, as well as the use of NATO troops, including French troops, to defend new members. Despite their support for enlargement, the French are closely divided about further expansion of the alliance within the next five years (43% favor, 41% oppose) Two-thirds oppose increasing the amount France currently pays to NATO to cover the costs of enlargement. In fact, a plurality believe new members themselves should take primary responsibility for managing these costs.; Opinion Analysis M-155-97